Temporomandibular Disorders and Fibromyalgia: A Narrative Review - Scarola, Roberta; Montemurro, Nicola; Ferrara, Elisabetta; Corsalini, Massimo; Converti, Ilaria; Rapone, Biagio (Open Access Macedonian Journal of Medical Sciences, 2021)
Temporomandibular disorder (TMD) and fibromyalgia (FM) have some clinical characteristics in common, for instance the chronic evolution, the pathophysiology incompletely understood and a multifactorial genesis. The incidence and the relationship between TMD and FM patients are the aims of this review. A MEDLINE and Pubmed search was performed for the key words “temporomandibular disorder” AND “fibromyalgia” from 2000 to present. A total of 19 papers were included in our review, accounting for 5449 patients. Ten studies, reporting a total of 4945 patients with TMD, showed that only 16.5% of these patients had diagnosis of FM, whereas 12 studies, reporting a total of 504 patients with FM, demonstrated that 77.0% of these patients had diagnosis of TMD. A comorbid relationship exists between TMD and FM. The complexity of both diseases shows the importance of a multimodal and interdisciplinary.